Surface modification of cellulose nanomaterial for urea biosensor application - Wan Elina Faradilla Wan Khalid,; Lee, Yook Heng; Mohamad Nasir Mat Arip, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Cellulose nanomaterial with rod-like structure and highly crystalline order, usually formed by elimination of the amorphous region from cellulose during acid hydrolysis. Cellulose nanomaterial with the property of biocompatibility and nontoxicity can be used for enzyme immobilization. In this work, urease enzyme was used as a model enzyme to study the surface modification of cellulose nanomaterial and its potential for biosensor application. The cellulose nanocrystal (CNC) surface was modified using 2,2,6,6-tetramethylpiperidine-1-oxyl radical (TEMPO)-mediated oxidation to introduce the carboxyl group at C6 primary alcohol. The success of enzyme immobilization and surface modification was confirmed using chemical tests and measured using UV-Visible spectrophotometer. The immobilization strategy was then applied for biosensor application for urea detection. Cyclic voltammetry (CV) and differential pulse voltammetry (DPV) techniques were used for electroanalytical characterization of the urea biosensor.